Natural Enemies, Mediated by Landscape and Weather Conditions, Shape Response of the Sorghum Agroecosystem of North America to the Invasive Aphid Melanaphis sorghi - Brewer, Michael J.; Elliott, Norman C.; Esquivel, Isaac L.; Jacobson, Alana L.; Faris, Ashleigh M.; Szczepaniec, Adrianna; Elkins, Blake H.; Gordy, J. W.; Pekarcik, Adrian J.; Wang, Hsiao-Hsuan; Koralewski, Tomasz E.; Giles, Kristopher L.; et al. (Frontiers in Insect Science, 2022)
The sorghum (Sorghum bicolor [L.]), agroecosystem of North America provided an opportunity to evaluate agroecosystem response to an invading insect, Melanaphis sorghi (Theobald (sorghum aphid) (previously published as Melanaphis sacchari Zehntner) (Hemiptera: Aphididae) onto a widely planted crop that experiences a range of agro-landscape and weather conditions. Initial risk assessments after M. sorghi’s invasion in the mid-2010s provided forecasts of range expansion and annual migration, which were based on aphid life history, extent of sorghum cultivation and susceptibility to M. sorghi, and weather (aphid-plant-weather [APW] risk scenario). A more comprehensive risk assessment proposed here brings top-down forces of M. sorghi-natural enemy interactions to the forefront as mediated by agro-landscape and weather conditions (aphid-enemy/landscape-weather mediated [AE/LW] risk scenario). A hypothesis of regional differences in aphids and natural enemies and sensitivity to agro-landscape and weather was tested using empirical data across five years and four regions (two in the U.S. Great Plains [South GP and North GP], one farther south (South), and one in the southeast U.S. [South E]). Natural enemies were widespread with two parasitoids and four coccinellid species common across regions, but regional variation in M. sorghi and natural enemy abundance was detected. The AE/LW risk scenario accounted for natural enemy abundance and activity that was highest in the South region, functioned well across agro-landscape and weather conditions and was accompanied by average low M. sorghi abundance (~23 M. sorghi per leaf). Positive correlations of natural enemy-M. sorghi abundance also occurred in the South GP region where M. sorghi abundance was low (~20 M. sorghi per leaf), and selected natural enemy activity appeared to be mediated by landscape composition. Melanaphis sorghi abundance was highest in the South E region (~136 aphids/leaf) where natural enemy activity was low and influenced by weather. The AE/LW risk scenario appeared suited, and essential in the South region, in assessing riskand sets the stage for further modelling to generate estimates of degree of influence of varying agro-landscape and weather conditions considered in the AE/LW risk scenario. Broadly, these findings are relevant in understanding agroecosystem resilience and recommending supportive management inputs in response to insect invasions.